Financial Empowerment of Farmers Through Agricultural Credit by Commercial Banks: A Descriptive Analysis - Balaji Dhanasekaran (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
According to the economic survey of India (2020-2021) stated that the total food production in the nation recorded at 296.65 million tonnes in the financial year and it has been increased by 11.44 million tonnes in the financial year 2019. The Indian government has set the goal to procure 42.74 million tonnes from the central pond in the financial year 2021. Similarly, the output of horticulture produce was estimated at 326.6 million tonnes in the financial year 2020. The sugar production has increased to 26.46 metric tonnes from 2019 to 2020. India is one of the prominent exporters of farm products across the world. The institutional loan is considered to play a very crucial role in the farm sector growth and development in India. The admission and delivery of rural credit are slanted in favour of healthier gifted regions and within the similar region posh towards better-off families. Agricultural credit is important to the farm credit system in India due to the capital accessibility of the farmers. It helps them to procure various raw materials such as seeds, fertilizers, land and other capital equipment. The agricultural credit is to be made accessible and available to agricultural and allied activities to promote agricultural output. The developing country like India, need greater support from the farmers for inclusive growth and development. This present study is followed the descriptive and analytical methods of research. Data for the present analysis is purely based on secondary data sources. The secondary information has been collected from various published reports such as NABARD and Reserve Bank of India for various years. During the 2004-2005 period, the target was aimed by the commercial banks was Rs.57000 crores. But the actual disbursement took place with Rs.81481 crores. It is evident from data sources that the disbursement amount was consistently increased from 2004-05 to 2007-08. The agricultural loan has been disbursed with Rs. 125477 crores, it was a huge increase as compared to the previous year disbursement of Rs. 81481 crores. It was reached 156850 crores rupees during 2007-2008